Peran Manajemen Sekolah dalam Mewujudkan Lingkungan Belajar yang Inklusif - Musdalifah; Hamzah, Elsa; Gaffar, Arjun; Kurniawan, Tomi (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
School leaders play an important role in creating an inclusive learning environment where all students, regardless of background or ability, can learn effectively and feel welcome. The aim of this research is to analyze strategies and practice school leadership in building an inclusive learning environment. A qualitative approach and case study design will be used. Data collection techniques will also be used through in-depth interviews with school principals, teachers and administrators, participant observation of the learning process and classroom interactions, as well as collection documentation regarding inclusive policies and practices. The data obtained was analyzed using thematic analysis techniques, including data transcription, coding, theme development, and interpretation to determine the school's efforts to create an inclusive learning environment, the challenges faced, and the solutions implemented.